Women and Politics - Basri, Hasan; El Adawiyah, Sa’diyah; Hernawan, Wawan (Opción, 2019)
The low participation of women in politics leads to a lack of women’s involvement in politics. Although there is already 30% quota of women’s representation in pol- itics, there are still not represented women’s voices in politics, especially regional leader. One way to increase women’s representation is through political communi- cation strategies involving women, affirmative action, women leadership and po- litical education for women. Strategies carried out through messages and medias used. Give woman opportunities to empower other woman. Hopefully Indonesian women can participate in the political frenzy. Not only as a sweetener but directly involved in practical politics.